Photodynamic inactivation of microorganisms present on complete dentures. A clinical investigation - Ribeiro, Daniela Garcia; Pavarina, Ana Claudia [UNESP]; Dovigo, Lívia Nordi [UNESP]; de Oliveira Mima, Ewerton Garcia; Machado, Ana Lucia [UNESP]; Bagnato, Vanderlei Salvador; Vergani, Carlos Eduardo [UNESP] (Springer London Ltd, 2012)
The aim of this study was to evaluate the effectiveness of photodynamic therapy (PDT) for the disinfection of complete dentures. Biofilm samples were collected from dentures of 60 denture users who were randomly divided into four experimental groups (n = 15 each): subjects whose maxillary dentures were sprayed with 50 and 100 mg/l of PhotogemA (R) suspension (groups P50S and P100S) and patients whose maxillary dentures were treated with 50 and 100 mg/l of PhotogemA (R) gel (groups P50G and P100G). Dentures with photosensitizers were left in the dark for 30 min (pre-irradiation time) and then irradiated with blue LED light at 37.5 J/cm(2) (26 min). Denture samples were taken with sterile cotton swab before (left side surfaces) and after (right side surfaces) PDT. All microbial material was diluted and plated on selective media for Candida spp., Staphylococcus mutans spp., streptococci and a non-selective media. After incubation (48 h/37A degrees C), the number of colony-forming units (cfu/ml) was counted. Microorganisms grown on selective media were identified using biochemical methods before and after PDT. The data were submitted to McNemar and Kruskal-Wallis tests (alpha = 0.05). No growth after PDT was observed in 60, 53, 47, and 40% of dentures from P100G, P50G, P100S, and P50S groups, respectively. When evidence of microorganisms' growth was observed, PDT regimens eliminated over 90% of microorganisms on dentures. This clinical study showed that PDT was effective for disinfecting dentures.
Keywords: Complete denture; Disinfection; Infection control; Photochemotherapy; Sterilization